Effects of Water Inrush from Tunnel Excavation Face on the Deformation and Mechanical Performance of Shield Tunnel Segment Joints. (28th December 2017) - Zhao, Tingsheng; Liu, Wen; Ye, Zhi
Abstract : Water inrush from the excavation face often occurs in the current shield construction of metro tunnels. In this study, the discontinuity of shield tunnel lining and the interaction between the tunnel segments, the grouting layer, and the surrounding rock are considered. Based on the 3D nonlinear contact theory, a hybrid model of the shield tunnel is constructed. Considering the fluid-solid coupling effect of water and soil, the influences of different water head differences on the mechanical performance and deformation of segments and joints in the shield tunnel are studied. The water gushing from the excavation face leads to vertical convergence of the cross-sectional area of the shield tunnel, and joint opening and dislocation result in sharp decrease of the waterproof capacity of joints. Meanwhile, the stress in the vicinity of segment joints increases sharply, and local cracks occur in the segment lining. The axial force, shear force, and bending moment in the joint bolt are also significantly increased. Based on the current metro standard and the computational results in this study, an emergency control criterion is put forward by means of controlling the discharge of water: the water head difference over the excavation face is required less than 4.6 M.